Cost of Illness for Patients with Arthritis Receiving Multidisciplinary Rehabilitation Care. (24th May 2011) - Grotle, Margreth; Hagen, Kåre Birger; Uhlig, Till; Aas, Eline
Abstract : Purpose . To describe healthcare consumption and costs prior to, during, and after multidisciplinary rehabilitation due to arthritis. Methods . 306 patients (age 18–75 years) with arthritis scheduled for multidisciplinary rehabilitation care in 9 rehabilitation centres and 4 rheumatology hospital departments were included and followed for 6 months. Costs were estimated in Euros (€ ) for the total sample and five clinical subgroups. Results . Healthcare costs ranged from€ 3, 033 to€ 91, 336 and were significantly higher at hospital departments compared to rehabilitation centres:€ 9, 722 (SD 5, 406) and€ 4, 250 (SD 1, 040). While total costs prior to and after rehabilitation were stable for those receiving rehabilitation at a hospital, there was a significant increase in costs for those being at a rehabilitation centre. Total mean costs were more than doubled when including social costs: from€ 32, 410 (95% CI 20, 074–37, 017) to€ 51, 491 (95% CI 49, 055–61, 657). Conclusions . Healthcare and social costs for arthritis rehabilitation were substantial both before and after a rehabilitation stay. It is important to explore methods to reduce the length of rehabilitation stay and production loss connected to rehabilitation of patients with rheumatic disease.